Efek Pemberian Daun Sirih (Piper sp.) Terhadap Pertumbuhan Candida albicans - Mira Kurnia (Medula, 2020)
Candidiasis is an infection caused by the Candida. The most common type of Candida that causes infection is Candida albicans. Part of body that generally can be attacked by Candida there are, the mouth, folds of the skin, the nail area and around the genitals, both male and female. Warm weather specially in Indonesia with a tropical climate and wear a tight cloths also poor personal hygiene can be a trigger for the growth of fungi, especially in moist body parts. Moreover, if supported by weak body immune conditions. Treatment using natural plants is rampant because it has fewer side effects. Betel leaf as a natural material that has often been used since a long time ago, it has been empirically proven to have antifungal effects, both fungistatic and fungicidal. Previous research has proven that betel leaf extract can inhibit the growth of Candida albicans that isolated in agar media. The potential of betel leaf as antifungal depends on the content of the extract which plays an important role, phenol compounds, flavonoids and tannins which are able to denaturate fungal proteins so as to prevent the proliferation of fungi. Provision of betel leaf extract (Piper sp.) with a minimum concentration of 25% can inhibit the growth of fungi and a maximum concentration of 100% can kill the growth of fungi Candida albicans.